Influence of Li co-doping on structural property of sol-gel derived terbium doped zinc oxide nanoparticles - Kumar P.; Yadav A.K.; Joshi A.G.; Bhattacharyya D.; Jha S.N.; Pandey P.C. (My University, 2025)
The presence of lattice distortion and defects in a composition leads towards a significant change in the optical, magnetic and electrical properties of the host material. In the present work, we have investigated the role of Li concentrations (0.25–1.0%) on structural property of Tb (1%) doped zinc oxide nanoparticles. A small concentration of terbium (1%) has been used to get minimum lattice distortion in the original structure of ZnO. To reduce the possible large lattice deformation on doping of Tb ion we have co-doped the material with Li. The crystalline nature of the sample has been confirmed by the XRD, Raman and FTIR studies of the material. The variation of bond length and lattice disorder in ZnO lattice due to the substitution of Tb and Li were studied from the EXAFS analysis at Zn K edge and Tb L3 edge. Interestingly, the study also shows that disorder decreases due to co-doping of Li in the considered system. Moreover, the oxidation states of all the elements present in the prepared samples were ascertained the XANES analysis. The morphology and particle size are calculated by TEM characterization. This work mainly emphasises on the structural property of synthesized compositions using these analyses. The study will also be helpful in exploring the change in optical, magnetic and electrical properties of the doped ZnO nanoparticles. © 2018 Elsevier Inc.